STRENGTHENING STUDENTS’ THEORETICAL KNOWLEDGE AND DEVELOPING PRACTICAL COMPETENCIES THROUGH EXPERIMENTATION - Shokir Xudoynazarovich Berdiyev (Bright Mind Publishing, 2025)
Physics is a discipline in which theory and practice are inseparably linked. Most physical laws, principles, and formulas are derived from experiments; therefore, experimentation plays an essential role in deepening students’ theoretical understanding and strengthening their practical competencies. This article analyzes how classroom experiments facilitate the comprehension of abstract concepts, support the formation of research skills, develop analytical and problem-solving competencies, and enhance students’ ability to connect theory with real-life phenomena. The paper further examines methodological approaches to organizing experimental activities, including demonstration experiments and open-inquiry laboratory work, highlighting their advantages and pedagogical implications. The study concludes that experimental learning environments significantly improve students’ conceptual understanding, scientific thinking, and readiness for practical application of knowledge.